2017
DOI: 10.1515/picbe-2017-0027
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for academic leadership towards increasing productivity in higher education institutions; business education case

Abstract: Abstract. Higher education institutions face a lot of challenges in the contemporary context. Labour market is s strict evaluator of the graduates' competences and skills and thus Main objectives of the study are the following: a). to define productivity in higher education institutions, on the basis of the academics' perceptions, as well as of students' perceptions; b). to provide a diagnosis of the current state of the prductivity in higher education institutions; c). to contribute to new clarifications on l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 2 publications
0
1
0
Order By: Relevance
“…In more recent researches conditioned by globalization processes the intercultural dimension of leadership competences is observed more and more distinctly. Summarising the ideas of the discussed authors, we can specify leadership competencies identified as fundamental (Hassanzadeh et al, 2015;Hooper & Potter, 2019;Iordache-Platis, 2017;Kessler, 2020;Kazakevych, 2020;Ruben, 2019). First of all, it is communicative skills/ language proficiency viewed in intercultural dimension.…”
Section: Problem Statementmentioning
confidence: 99%
“…In more recent researches conditioned by globalization processes the intercultural dimension of leadership competences is observed more and more distinctly. Summarising the ideas of the discussed authors, we can specify leadership competencies identified as fundamental (Hassanzadeh et al, 2015;Hooper & Potter, 2019;Iordache-Platis, 2017;Kessler, 2020;Kazakevych, 2020;Ruben, 2019). First of all, it is communicative skills/ language proficiency viewed in intercultural dimension.…”
Section: Problem Statementmentioning
confidence: 99%